OPTIMIZING API PERFORMANCE IN CRUISE BOOKING SYSTEMS - Jayaram Bhogi (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article explores comprehensive strategies for optimizing API performance in cruise booking systems, focusing on the challenges and solutions in handling high-volume transactions during peak seasons. The article examines various aspects, including asynchronous processing, intelligent request batching, dynamic load balancing, and advanced caching strategies within the context of modern cruise reservation platforms. The article also looks into integration patterns for different user groups, security considerations, and the implementation of agile methodologies for continuous improvement. Through an article of real-world implementations and industry best practices, this paper provides insights into building robust, scalable, and efficient API architectures for the cruise industry.